Avaliação da equivalência terapêutica das cópias genéricas do mesilato de imatinibe no tratamento inicial da Leucemia Mieloide Crônica em primeira fase crônica em um centro de referência - Quixadá, Acy Telles de Souza (2016)
Imatinib has revolutionized the treatment of Chronic Myeloid Leukemia by modifying its natural history. Several studies have demonstrated that achieving and maintaining major molecular response is a goal that, when achieved, offers the patient life expectancy similar to that of the general population. However, there are few consistent data on the efficacy and adverse effects of generic imatinib presentations. This study aimed to evaluate the response to treatment with generic imatinib 400 mg QD day for adult patients with chronic phase CML at a university hospital, and compare it with the group that used the brand imatinibe. The study, retrospective and observational, analyzed the records of 80 patients, 40 in each group, without experimental step. The comparative analysis included 29 patients who used the brand medication and 32 who used the generic presentation for 12 consecutive months. Treatment response was assessed according to the European Leukemia Network (ELN) criteria. We analyzed the results of the monitoring tests for therapeutic response at three, six and twelve months of treatment with the brand product and generic copy. The statistical analysis used the Statistical Package Program for Social Sciences (SPSS) 22.0, and applied Kolmogorov Smirnov, Mann Whitney and Log-rank Mantel-Cox tests, with 5% significance level. With the original medicine, at three months, the optimal treatment response (BCR-ABL1IS ≤ 10%) was achieved by 62% (18/29) of patients. At six months, 41.4% (12/29) hit the optimal response with the reduction of at least 2 logs (BCR-ABL1IS ≤ 1%). Finally, at 12 months, 48.2% (14/29) of patients achieved major molecular response (MMR) which corresponds to the BCR-ABL1IS ≤ 0.1%. With the generic medication, major response at three months was achieved by 62.5% (20/32). At six months, 71.9% of patients achieved an optimal response (23/32). Finally, at twelve months, 53.1% (17/32) of patients achieved the target of RMM. A slight increase in the prevalence of non-hematological adverse events of the gastrointestinal tract in the generic group was observed. The results of this study suggests that the response profile of adult patients with CP-CML using imatinib 400 mg QD in its generic presentation is comparable in the first evaluation and even surpasses the results obtained with the brand medication. We conclude that, in this sample, does not exist inferiority of the drug in its generic presentation.